The role of neural tension in hamstring flexibility - McHugh, M.P.; Johnson, C.D.; Morrison, R.H. (Scandinavian journal of medicine & science in sports, 2012)
Resistance to stretch, electromyographic (EMG) response to stretch, stretch discomfort and maximum range of motion (ROM) were measured during passive hamstring stretches performed in the slump test position (neural tension stretch) and in the upright position (neutral stretch) in eight healthy subjects. Stretches were performed on an isokinetic dynamometer at 5°/s with the test thigh flexed 40° above the horizontal, and the seat back at 90° to the horizontal. Surface EMG signals were recorded from the medial and lateral hamstrings during stretches. Knees were passively extended to maximum stretch tolerance with test order (neural tension vs neutral) alternated between legs. For neural tension stretches, the cervical and thoracic spine were manually flexed. Maximum ROM was 8° less for the neural tension stretch vs the neutral stretch (P<0.01). Resistance to stretch was 14–15% higher for the neural tension stretch vs the neutral stretch (P<0.001) at common joint angles in the final third of ROM. Stretch discomfort and EMG response were unaffected by neural tension. In conclusion, an increased passive resistance to stretch with the addition of neural tension during passive hamstring stretch despite no change in the EMG response indicates that passive extensibility of neural tissues can limit hamstring flexibility.